Eficiência energética em prédios públicos como instrumento de política pública: uma análise no âmbito governamental do Estado de Goiás - Figuerêdo, Renata Guimarães (2023)
Electric energy is an indispensable resource for the economic and social development of a country. Its rational use, following the principles of Energy Efficiency, contributes to a better balance and security in the relationship between generation and demand, reducing waste, consumption and the risk of supply. In the field of buildings, Energy Efficiency is a relevant attribute of sustainability in architecture. Thus, the objective of this dissertation is to investigate and analyze federal laws, programs and public policies to promote energy efficiency in buildings, verifying and comparing their possible consequences in the state of Goiás, in order to evaluate and propose possible actions and policies directed specifically to the state public buildings, in order to promote and improve the energy and environmental performance of these buildings. Moreover, the technical potential for energy savings both in existing buildings and in new buildings that include energy efficiency strategies is significant, impacting positively on energy conservation and, in the case of public works, in the reduction of government spending, as well as in the management and efficiency of public administration, with effective economic, environmental and social gains.